Simultaneous magnetotelluric and magnetovariational soundings of the northern part of the Dnieper-Donets trough - Kushnir, A.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
The main purpose is to study a geoelectric structure of the lithosphere of the northern part of the Dnieper-Donets trough using modern methods (techniques) of synchronous electromagnetic sounding based on natural fields. Reliable tipper estimates for periods of geomagnetic variations 30–3500 s, horizontal MV responses 30–10000 s and impedance parameters 30–10000 s were obtained. Qualitative interpretation of MTS curves showed that the maximum depths to the upper edge of the conductor are in the northern end of the southern slope of DDT and Bragin-Loyev uplift, which vary from 40–30 km to 18 km and correspond to the north-eastern end of the Prypyat conductivity anomaly. In the central part of the DDT, the upper edge of the conductor occurs at depths of 3–5 km and is explained by the transition zone of sedimentary rocks and the decompacted rocks of the foundation. On the slopes of DDT, the depth of the upper edge of the conductor is 8 km.